Genetic polymorphism of Streptococcus mutans strains associated with incomplete caries removal - Duque, Cristiane [UNESP]; de Cássia Negrini, Thais [UNESP]; Sacono, Nancy Tomoko [UNESP]; Gomes Boriollo, Marcelo Fabiano; Hofling, José Francisco; Hebling, Josimeri [UNESP]; Palomari Spolidorio, Denise Madalena [UNESP] (My University, 2009)
Aim: Despite the antibacterial properties of dental materials, the survival of residual bacteria under restorations has been demonstrated after incomplete caries removal. The aim of this study was to evaluate the genetic polymorphism of Streptococcus mutans strains isolated from deep dentinal lesions before and three months after incomplete caries removal. Methods: Samples of carious dentin were collected from 33 primary and/or permanent molars before and after indirect pulp treatment and processed for microbiological isolation of mutans streptococci (MS). After three months of the dental treatment, positive cultures for MS were detected in only ten of these teeth. DNA of MS isolates were obtained and subjected to polymerase chain reaction (PCR) for identification of S mutans. The arbitrary primed-PCR method (primer OPA-13) was used to detect the genetic polymorphism of S. mutans strains. Results: Identical or highly related S. mutans genotypes were observed in each tooth, regardless of the collect. Considering each tooth separately, a maximum of nine genotypic patterns were found in each tooth from all the collects. In addition, at least one genotypic pattern was repeated in the three collects. Genetic diversity was observed among the S. mutans isolates, obtained from different teeth after three months of the dental treatment. Conclusions: The persistence of identical genotypic patterns and the genetic similarity among the isolates, from the same tooth in distinct collects, showed the resistance of some S. mutans strains after incomplete caries removal treatment.
Keywords: Dental caries; Genetic; Polymerase chain reaction; Polymorphism; Streptococcus mutans